Howard Hiatt: How This Extraordinary Mentor Transformed Health with Science and Compassion - Rosenberg (MIT Press, 2018)
Monograph
fulltext
Keywords: Bioengineering; Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing